2020
DOI: 10.1186/s12887-020-2015-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying children exposed to maltreatment: a systematic review update

Abstract: Background: Child maltreatment affects a significant number of children globally. Strategies have been developed to identify children suspected of having been exposed to maltreatment with the aim of reducing further maltreatment and impairment. This systematic review evaluates the accuracy of strategies for identifying children exposed to maltreatment. Methods: We conducted a systematic search of seven databases: Medline, Embase, PsycINFO, Cumulative Index to Nursing and Allied Health Literature, Cochrane Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 64 publications
1
27
0
4
Order By: Relevance
“…However, it is important to reflect upon the suggestion from participants in this study that issues of family violence are unlikely to be reported or identified at the outset of the therapeutic relationship. In addition, the World Health Organization Mental Health Gap Action Programme (World Health Organization, ) as well as recent reviews by Bailhache, Leroy, Pillet, and Salmi (), and McTavish, Gonzalez, et al () and McTavish, Kimber, et al () indicate insufficient evidence detailing whether the utilization of such screening tools does more good than harm. Similarly, evaluation of these tools' sensitivity and specificity suggests that a large proportion of children are falsely identified as being maltreated when using these tools and these tools rarely evaluate CEA and CEIPV (McTavish et al, McTavish, Gonzalez, et al, , McTavish, Kimber, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to reflect upon the suggestion from participants in this study that issues of family violence are unlikely to be reported or identified at the outset of the therapeutic relationship. In addition, the World Health Organization Mental Health Gap Action Programme (World Health Organization, ) as well as recent reviews by Bailhache, Leroy, Pillet, and Salmi (), and McTavish, Gonzalez, et al () and McTavish, Kimber, et al () indicate insufficient evidence detailing whether the utilization of such screening tools does more good than harm. Similarly, evaluation of these tools' sensitivity and specificity suggests that a large proportion of children are falsely identified as being maltreated when using these tools and these tools rarely evaluate CEA and CEIPV (McTavish et al, McTavish, Gonzalez, et al, , McTavish, Kimber, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…First, universal screening for child maltreatment is not recommended at any point during FBT. There is no evidence that universal screening for child maltreatment leads to reduced harm, reduced exposure, or optimal outcomes among those who have experienced child maltreatment (60)(61)(62)(63). Second, an explicit discussion about the limits of confidentiality with each family member is needed.…”
Section: Principles For Safely Recognizing Child Maltreatment In Fbtmentioning
confidence: 99%
“…Nearly a decade later, McTavish et al (2020, p. 10) confirm that the situation remains unchanged: '[I]t is still difficult to assess the accuracy of instruments to identify potential child maltreatment as there is no gold standard for identifying child maltreatment'. The systematic reviews carried out by Bailhache et al (2013) and McTavish et al (2020) align with regard to the fact that high numbers of false positives and negatives resulted from the use of screening tools for identifying potential child maltreatment.…”
Section: Introductionmentioning
confidence: 99%
“…Hoft andHaddad (2017) also note that SVAC screening tools in particular (those available between 1995 and 2016) had a tendency to draw on assessment domains that were not definitive for such abuse, raising questions about their reliability. McTavish et al (2020) extend the conversation beyond screening tools alone, reminding us that the process and context in which screening occurs are as important as the tools themselves. As they emphasise: '[I]t is unclear how these tools are being used in practice, or how they will in the future be used in practice.…”
Section: Introductionmentioning
confidence: 99%